1998
DOI: 10.1038/sj.jhh.1000664
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of elderly patients with isolated systolic hypertension with isosorbide dinitrate in an asymmetric dosing schedule

Abstract: Nitrates decrease pulse pressure more than mean arterial pressure (MAP) and are advocated for the treatment of isolated systolic hypertension (ISH). Nitrates show drug tolerance during chronic treatment so an asymmetric dosing regimen may prevent loss of effect of nitrates. This study investigates the anti-hypertensive effect of isosorbide dinitrate (ISDN) given in a twice daily asymmetric dosing regimen in elderly patients with ISH.After a 6-week placebo run-in period, patients entered the double-blind study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…DBP and heart rate values did not differ from those for placebo. The other study 48 confirmed the reduction in office PP with ISDN after 8 weeks of treatment, without a reduction in DBP. In addition, ambulatory PP decreased with ISDN, whereas it did not change during placebo.…”
Section: Changes In Stiffness and Wave Reflections Induced By Nitratessupporting
confidence: 66%
See 3 more Smart Citations
“…DBP and heart rate values did not differ from those for placebo. The other study 48 confirmed the reduction in office PP with ISDN after 8 weeks of treatment, without a reduction in DBP. In addition, ambulatory PP decreased with ISDN, whereas it did not change during placebo.…”
Section: Changes In Stiffness and Wave Reflections Induced By Nitratessupporting
confidence: 66%
“…Besides the possible tachyphylaxia, the wellknown side effect of headache might be a disadvantage for the common use of nitrates. Although in 1 study in isolated systolic hypertension side effects were not significantly increased with ISDN than with placebo, 47 in the other study, 48 Ͼ20% of patients dropped out because of headache.…”
Section: Changes In Stiffness and Wave Reflections Induced By Nitratesmentioning
confidence: 99%
See 2 more Smart Citations
“…171,172 Nitrates do not substantially affect stiffness of the proximal aorta, yet they reduce PP more selectively than other vasoactive drugs by inducing only minimal changes in diastolic or mean pressure. 173,174 This may occur by a more selective effect on venodilation 175,176 and attenuation of peripheral wave reflections during systole. 176,177 Long-term effects have been limited by development of nitrate tolerance, among other potential mechanisms.…”
Section: Can We Intervene? Reducing Vascular Stiffeningmentioning
confidence: 99%